The imprisonment of Dissidents in mental Institution in the Soviet Union 1918–1988 - Kuklytė, Birutė (Genocidas ir rezistencija, 2025)
The functioning of a “political psychiatry” machine began under Stalin, and this practice reached the highest level in the 1960s. The KGB and psychiatrists made up a smooth tandem in the practice of political psychiatry, but this issue was mainly encoded in the wrong laws.